Pengaruh Konseling Terhadap Kepatuhan Pasientuberculosis Di Puskesmas Langsa Lama Kota Langsa - Nurbaya, Siti; Nuriyanti Sirait; Yanti Musyawarah (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
The consequences of non-compliance with long-term treatment are deteriorating health and increasing treatment costs. Non-adherence of TB sufferers to treatment causes low cure rates, high mortality rates and increased recurrence and what is more fatal is the occurrence of germ resistance to several anti-tuberculosis drugs, so TB disease is very difficult to cure. The purpose of this study was to determine the effect of counseling on medication adherence. This type of research is a correlation analytic research with cross sectional method. The population in this study were TB sufferers with a sample of 35 people. The data were obtained using a questionnaire and the data were analyzed using the Chi-Square statistical test. The results showed that 1) the level of patient compliance in taking drugs in patients with tuberculosis at the Langsa Lama Health Center was in the majority with high adherence 2) the majority of counseling was given to patients with tuberculosis at the Langsa Lama Health Center in the good category, 3) there was an influence of counseling on patient compliance.